Resilient households and welfare state institutions : portuguese national report - Capucha, L. (2016)
The welfare state is a recent development in Portugal, just as it is in many other Southern and Eastern European countries. Portugal’s late industrialisation resulted in the beginnings of protection against social risks being sketched out during the First Republic (1910-26), when laws were passed establishing this protection along Bismarckian lines; however, these laws were never enforced. The social protection that did exist consisted of a network of local and professional mutualist associations covering a very limited range of risks while paying out very low benefits (Pereira M. H., 2012).